2016
DOI: 10.18632/oncotarget.9745
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of DNA demethylase and histone methyltransferase upregulates Nrf2 in 5-fluorouracil-resistant colon cancer cells

Abstract: We recently reported that DNA demethylase ten-eleven translocation 1 (TET1) upregulates nuclear factor erythroid 2-related factor 2 (Nrf2) in 5-fluorouracil-resistant colon cancer cells (SNUC5/5-FUR). In the present study, we examined the effect of histone modifications on Nrf2 transcriptional activation. Histone deacetylase (HDAC) and histone acetyltransferase (HAT) were respectively decreased and increased in SNUC5/5-FUR cells as compared to non-resistant parent cells. Mixed-lineage leukemia (MLL), a histone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 36 publications
1
44
0
Order By: Relevance
“…Nuclear accumulation of NRF2 was also correlated with a poor survival of lung SqCC and pancreatic adenocarcinomas and a worse progression free survival (PFS) in patients treated with surgery only [ 44 47 ]. Aberrant NRF2 activation due to KEAP1 alterations is also reported as one of the molecular mechanisms of chemoresistance of gallbladder cancer under 5-FU-based regimen and of colorectal cancer under demethylase and methyltransferase treatments [ 20 , 48 , 49 ].…”
Section: The Genetic Deregulation Of Keap1/nrf2 Signaling and Its mentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear accumulation of NRF2 was also correlated with a poor survival of lung SqCC and pancreatic adenocarcinomas and a worse progression free survival (PFS) in patients treated with surgery only [ 44 47 ]. Aberrant NRF2 activation due to KEAP1 alterations is also reported as one of the molecular mechanisms of chemoresistance of gallbladder cancer under 5-FU-based regimen and of colorectal cancer under demethylase and methyltransferase treatments [ 20 , 48 , 49 ].…”
Section: The Genetic Deregulation Of Keap1/nrf2 Signaling and Its mentioning
confidence: 99%
“…They found that elevated reactive oxygen species (ROS) level induced by 5-FU activates TET (ten-eleven translocation) DNA demethylases and produces a hypomethylation of the NFE2L2 promoter with consequent activation of NRF2 translation. This, in turn, upregulates the expression of the antioxidant enzymes and generates the resistance to 5-FU in cancer cells [ 48 , 49 ].…”
Section: The Aberrant Methylation Of the Keap1-nrf2 Axis And Its Tmentioning
confidence: 99%
“…Treatment with 2-deoxy-D-glucose (2-DG), a glucose-mimic inhibitor of glycolysis, reduces miR-483-3p expression and increases sensitivity to 5-FU-induced apoptosis. In 5-FU resistant SNUC5 colon cancer cells, OGT is overexpressed and interacts strongly with oxidative stress-activated ten-eleven translocation methylcytosine dioxygenase 1 (TET1) and histone H3 lysine 4 (H3K4) methyltransferase SET1/COMPASS (complex proteins associated with SET1) complex involved in the activation of gene expression [ 161 ]. O -GlcNAcylation is known to modulate recruitment, stability and activity of some chromatin regulators [ 162 ].…”
Section: Glycosylation Alterations In Colorectal Cancer Cells and Resmentioning
confidence: 99%
“…Particularly, OGT-mediated O -GlcNAcylation stabilizes TET1 [ 163 ] and OGT interacts preferentially with TET1 at gene promoters in close proximity of CpG-rich transcription start sites [ 164 ]. The multiprotein complex is recruited at the promoter region of nuclear factor erythroid 2-related factor 2 (Nrf2), a major transcription factor driving antioxidant enzymes expression; the upregulation of the transcription factor would be responsible for 5-FU resistance [ 161 ] (Figure 4E ; Table 1 ). A genome-wide mRNA expression profiling of the National Cancer Institute NCI-60 human tumor cell lines screen, comprising seven different colon cancer cell lines, revealed that OGT expression is negatively correlated with sensitivity to fluorodeoxyuridine monophosphate (FdUMP), the active metabolite of 5-FU responsible for TS inhibition (Figure 3 ; Table 1 ).…”
Section: Glycosylation Alterations In Colorectal Cancer Cells and Resmentioning
confidence: 99%
“…TETs-OGT/ O -GlcNAcylation is involved in some cancer development. In 5-fluorouracilresistant colon cancer cells (SNUC5/5-FUR), highly expressed OGT binds to TET1 and recruits to the Nrf2 (nuclear factor erythroid 2-related factor 2) promoter region, suggesting the role of OGT in TET1-mediated Nrf2 expression (Kang et al, 2016 ). Taken together, TETs proteins in collaboration with OGT play a critical role in regulating chromatin structure and gene transcription.…”
Section: Crosstalk Between O -Glcnacylation and Epmentioning
confidence: 99%